Genome size in three species of glandularia and their hybrids - Ferrari, M. R. (2019)
In this work the relationship between genome size of Glandularia species and the meiotic configurations found in their hybrids are discussed. Glandularia incisa (Hook.) Tronc., growing in two localities of Corrientes and Córdoba provinces, Argentina, with different ecological conditions, showed inter-population variability of the 2C-value. The DNA content found in the Corrientes locality (2.41 pg) was higher than that obtained in the Córdoba locality (2.09 pg) which has more stressful environmental conditions than the former. These values are statistically different from those that were found in Glandularia pulchella (Sweet) Tronc. from Corrientes (1.43 pg) and in Glandularia perakii Cov. et Schn from Córdoba (1.47 pg). The DNA content of the diploid F1 hybrids, G. pulchella × G. incisa and G. perakii × G. incisa, differed statistically from the DNA content of the parental species, being intermediate between them. Differences in the frequency of pairing of homoeologous chromosomes were observed in the hybrids; these differences cannot be explained by differences in genome size since hybrids with similar DNA content differ significantly in their meiotic behavior. On the other hand, the differences in the DNA content between the parental species justify the presence of a high frequency of heteromorphic open and closed bivalents and univalents with different size in the hybrids.